Special issue. - Sarat, Austin (Studies in law, politics, and society ;, 2014)
In The beautiful prison incarcerated Americans and prison critics seek to imagine the prison as something better than a machinery of suffering. From personal testimony to theoretical meditation these writers explore and confront the practical and cultural limits the prison places on its transformation into a socially constructive institution.